\[\boxed{\text{269\ (269).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[f(x) = \left\{ \begin{matrix} \frac{4}{x},\ \ x < - 1\ \ \ \ \ \ \ \ \\ \frac{x}{4},\ \ - 1 \leq x \leq 1 \\ \frac{4}{x},\ \ x > 1\ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[y = \frac{4}{x}\]
\[x\] | \[1\] | \[2\] | \[4\] | \[- 1\] | \[- 2\] | \[- 4\] |
---|---|---|---|---|---|---|
\[y\] | \[4\] | \[2\] | \[1\] | \[- 4\] | \[- 2\] | \[- 1\] |
\[y = \frac{x}{4}\]
\[x\] | \[0\] | \[8\] |
---|---|---|
\[y\] | \[0\] | \[2\] |
\[нули\ функции:x = 0.\]
\[f(x) > 0\ на\ (0;\ + \infty).\]
\[f(x) < 0\ на\ ( - \infty;0).\]
\[возрастает\ на\ \lbrack - 1;1\rbrack.\]
\[убывает\ на\ ( - \infty;\ - 1)\ и\ \]
\[(1;\ + \infty)\text{.\ }\]
\[\boxed{\mathbf{269.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ \sqrt{x + 6} + \frac{1}{x - 4}\]
\[\left\{ \begin{matrix} x + 6 \geq 0 \\ x - 4 \neq 0 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} x \geq - 6 \\ x \neq 4\ \ \ \\ \end{matrix} \right.\ \]
\[D(y) = \lbrack - 6;4) \cup (4; + \infty).\]
\[2)\ \frac{1}{\sqrt{21 - 3x}} + \frac{1}{x^{2} - 9}\ \]
\[\left\{ \begin{matrix} 21 - 3x > 0 \\ x^{2} - 9 \neq 0\ \ \ \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} - 3x > - 21 \\ x \neq \pm 3\ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} x < 7\ \ \ \\ x \neq 3\ \ \ \\ x \neq - 3 \\ \end{matrix}\ \right.\ \]
\[D(y) = ( - \infty; - 3) \cup ( - 3;3) \cup (3;\ 7).\]